Analisis Konsep Perjanjian (NOOMINAT) Bernama dalam Perspektif Hukum Perdata - Hidayanto, Nur Jantra; Febrian, Fazl Mawla; Dwiki, Farel; Sulastri, Sulastri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Named agreements (noominat) are a type of agreement that has been explicitly regulated in laws and regulations, especially in the Civil Code (KUHPer). This study aims to analyze the basic concept of named agreements, their legal characteristics, and their implementation in contractual relations in Indonesia. This study uses a normative legal approach with a descriptive legal analysis method. The results of the study indicate that named agreements have a significant position in the civil law system because they include important agreements such as buying and selling, renting, and lending. The characteristic of named agreements lies in the clarity of the norms that regulate the rights and obligations of the parties, thus providing legal certainty. However, amidst the development of community needs, challenges arise regarding the flexibility and adaptation of named agreements to the dynamics of modern law. This study highlights the importance of regulatory reform to increase the relevance of named agreements in the digital era and globalization.